How To Get Customers Satisfication The Travel Agent Competition In Bekasi, Indonesia (Case Study of PT Dos Ni Roha Java) - Timbo P. Simanjuntak; Supriyanto; Doddy Kurniawan (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Bekasi is a city that has a very high population density. This population density is also an opportunity for business people in Bekasi to start their business because Bekasi has high business potential. The large number of migrants in Bekasi has made the Travel Agent Business a promising business. One of the travel agents in Bekasi is PT DOS NI ROHA JAVA. The purpose of this research is to determine the effect of price and promotion on customer satisfaction in Bekasi, Indonesia. The research uses a quantitative method, with an Accidental Sampling sampling technique using a questionnaire distributed to respondents with a total of 106 respondents, then the data results are processed using the SPSS 26 data processing application. The results of the research show that Price and Promotion have an influence on PT DOS NI ROHA JAVA Customer Satisfaction